Competing Deactivation Channels for Excited π-Stacked Cytosines - Shuai Yuan; Huiling Hong; Gang Wang; Wenying Zhang; Yusheng Dou; Glenn V. Lo (International Journal of Photoenergy)
The deactivation of π-stacked cytosine molecules following excitation by ultrashort laser pulses was studied using semiclassical dynamics simulations. Another deactivation channel was found to compete with a previously reported path that led to dimerization. For both pathways, the initial excited state was found to form a charge-separated neutral exciton state, which forms an excimer state by charge transfer. When the interbase distance becomes less than 3 Å, charge recombination occurs due to strong intermolecular interaction, ultimately leading to an avoided crossing. Results indicate that the C2–N1–C6–C5 and C2′–N1′–C6′–C5′ dihedral angles play a significant role in the vibronic coupling between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO). Vibrational energy distribution determines the fate of the excimer at the avoided crossing. Higher-amplitude vibration of C5 or C6 atoms leads to a nonadiabatic transition to the electronic ground state (a photophysical pathway); otherwise, a chemical reaction leading to the formation of cyclobutane type dimer occurs as found in earlier studies. The S1 and S0 potential energy surfaces calculated at TD-DFT level and the simulated trajectories were found to be consistent with CASPT2 results.